2022
DOI: 10.1038/s41419-022-04708-w
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells protect against ferroptosis via exosome-mediated stabilization of SLC7A11 in acute liver injury

Abstract: Mesenchymal stem cells (MSCs) have attracted interest for their potential to alleviate liver injury. Here, the protective effect of MSCs on carbon tetrachloride (CCl4)-induced acute liver injury (ALI) was investigated. In this study, we illustrated a novel mechanism that ferroptosis, a newly recognized form of regulated cell death, contributed to CCl4-induced ALI. Subsequently, based on the in vitro and in vivo evidence that MSCs and MSC-derived exosomes (MSC-Exo) treatment achieved pathological remission and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 43 publications
3
75
0
Order By: Relevance
“…Considerable evidence has suggested that exosomes have important roles not only in the pathogenic progression of chronic liver disease but also in the initial onset of acute liver injury. [113][114][115] HSC-derived exosomes are considered to be one of the most prominent indicators of the degree of liver damage, 21 which is supported by a series of experimental studies. To date, most investigations of HSC-derived exosomes on liver damage have focused on chronic liver injury and persisting consequences that result in acute liver injury.…”
Section: Acute Liver Injurymentioning
confidence: 89%
“…Considerable evidence has suggested that exosomes have important roles not only in the pathogenic progression of chronic liver disease but also in the initial onset of acute liver injury. [113][114][115] HSC-derived exosomes are considered to be one of the most prominent indicators of the degree of liver damage, 21 which is supported by a series of experimental studies. To date, most investigations of HSC-derived exosomes on liver damage have focused on chronic liver injury and persisting consequences that result in acute liver injury.…”
Section: Acute Liver Injurymentioning
confidence: 89%
“…Tan et al proved that MSC-exos may promote xCT/GPX4-mediated activated hepatic stellate cells ferroptosis through the delivery of BECN1 [ 65 ]. Lin et al also concluded that MSC-exos might alleviate ferroptosis via the CD44 and OTUB1-mediated stabilization of SLC7A11 [ 66 ]. Therefore, we speculated that ERC-exos regulates ferroptosis primarily through delivering its rich proteins and miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is involved in the progression of numerous diseases, and it has been proved that MSC-exos could attenuate diseases through inhibiting ferroptosis. Studies have found that MSC-exos could deliver its miRNA and proteins that act on genes participating in iron metabolism and lipid peroxide process to regulate [66]. Therefore, we speculated that ERC-exos regulates ferroptosis primarily through delivering its rich proteins and miRNA.…”
Section: Stem Cells Internationalmentioning
confidence: 96%
“…For example, it was recently shown that MSCs are capable of inhibiting the production of lipid peroxidation and alleviating ferroptosis both in vitro and in vivo . The authors also demonstrated that MSC-derived exosomes are involved in the underlying mechanisms of the effect of MSCs on ferroptosis, which could significantly downregulate the expression of prostaglandin-endoperoxide synthase 2 and promote SLC7A11 expression [ 38 ]. Similarly, the suppressive effect of MSCs on ferroptosis was seen in neuronal cells [ 39 ].…”
Section: Ferroptosis and Bone Homeostasismentioning
confidence: 99%